Marcas viscerais: significado profundo da marca Laboratório Fantasma - Pereira, Raul de Santa Helena (2021)
This research aims to analyze the process of building activist visceral brands with deep meaning, those that manage to transcend the uniquely rational and tangible aspects, unveiling, defining and managing a set of elements of deep meaning (high purpose, archetypal energy, beliefs and values, among others) with consistency in time, discourse and effective actions. Thus, they establish more intimate and true relationships with society and main stakeholders and share the same high purpose, beliefs and values with society, especially with their priority stakeholders, honoring this communion in effective actions, defining a greater cause. and an obvious problem for society to then directly contribute to the improvement of indicators associated with this problem. The research object of study was the case of the Laboratório Fantasma brand, a creative cultural collective founded by the brothers Leandro and Evandro de Oliveira independently as a record label, audiovisual producer, events and fashion and street attitude brand. Based on bibliographic research and on the broad and deep documentary survey of this case, in particular, in particular, we seek to investigate the elements that define these activist visceral marks with deep meaning, such as high purpose, non-negotiable beliefs and values, energy archetypal, among others. It analyzes how the values and beliefs contained in the hip-hop movement, in the ancestral African philosophy of Ubuntu and in the cause of combating structural racism and the necropolitics project of the Brazilian State helped to forge the elements that make up the brand's universe